Perylene derivatives with large two-photon-absorption cross-sections for application in optical limiting and upconversion lasing - Oliveira, S. L.; Correa, D. S.; Misoguti, L.; Constantino, CJL; Aroca, R. F.; Zilio, S. C.; Mendonca, C. R. (Wiley-Blackwell, 2005)
Perylene tetracarboxylic derivatives (PTCDs) display exceptionally high two-photon absorption (2PA) cross-sections (6, see Figure). In addition, the 2PA saturation behavior and strong two-photon-pumped fluorescence suggest that PTCD compounds may be attractive candidates for applications in optical limiting and two-photon-pumped upconversion lasing.